In Vitro Effect of Porcelain Firing Cycle and Different Thicknesses of IPS E.max CAD Core on Marginal Accuracy of All-Ceramic Restorations - Ezatollah Jalalian; Arash Zarbakhsh; Zahra Mohtashamrad; Nazanin Nourbakhsh; Esmat Jafarpour (Tehran University of Medical Sciences, 2016)
Objectives: Marginal adaptation is important for long-term success of full-coverage restorations. The aim of this study was to determine the effect of porcelain firing cycle and different thicknesses of IPS e.max core on marginal accuracy of all-ceramic restorations. Materials and Methods: A standard stainless steel die with 0.8 mm classic chamfer finish line and 10° taper was used in this in vitro study. An impression was taken from the stainless steel die to fabricate 20 epoxy resin dies, which were then scanned and IPS e.max CAD cores were fabricated using computer-aided design/computer-aided manufacturing (CAD/CAM) technique in two groups of 10 with  0.7 mm (group A) and 0.4mm (group B) core thickness. Copings were then placed on their respective dies and randomly numbered. The amount of marginal gap was measured in 10 points under a stereomicroscope (×90 magnification) before and after porcelain veneering. Results: The mean gap in 0.7mm and 0.4mm core thicknesses was 15.62±2.55µm and 19.68±3.09µm before porcelain firing and 32.01±3.19µm and 35.24±3.8µm after porcelain firing. The difference in marginal gap between the two thicknesses was significant before porcelain firing but not significant after veneering. Significant differences were also found in the marginal gap before and after porcelain veneering in each group. Conclusion: The porcelain firing cycle increases marginal gap in IPS e.max CAD restorations; 0.3 mm decrease in core thickness slightly increased marginal discrepancy, however it was not significant.